Genetic diversity of tartary buckwheat based on the sequence analysis of PAL - Li, M.; Zhang, Z.; Wu, B.; Gao, J.; Li, Y. (Ingenta Connect, 2017)
Tartary buckwheat is widely cultivated in different areas of China and gradually evolved into genetic diversity. In order to study and utilize the tartary buckwheat, the PAL gene differences of the tartary buckwheat were analyzed on 67 samples,which were collected from different provinces of China( including the north region and the southwest region) and the Nepal region. We amplified the PAL gene by PCR and then acquired the sequence results.Based on the sequences,genetic diversity was analyzed and cluster of analysis of 67 samples was also carried out by NJ method. The results showed that after aligning and splicing, the length the PAL sequence was 2011 bp in the matrix,the variable sites was 160,while the parsimony informative sites was 33,accounting for 7. 9% and 1. 64% of the total length, respectively. Variable type were mainly base transition and base transversions. Variable site mainly concentrated in the region of 600-1200,which was the site of the N-terminal of the exon-2. The intra-specific mean distance of the Sichuan group was 0. 016,while the tartary buckwheat from Inner Mongolia group showed that the intra-specific mean distance was 0. 002. And it revealed that there was a significant difference among the tartary buckwheat resources in genetics diversity from different geographic origins. We checked the 67 PAL sequences using software. And it showed that the average value of the Nucleotide polymorphism( p) and the average heterozygosity( ?) were 0. 0034 and 0. 0143, respectively. The Nucleotide polymorphism( p) value in samples from Sichuan was the highest( 0. 0148) . From the phylogenetic tree, it indicated that the 67 samples from the different province could be clustered into seven categories. And the 5 sample in Tibet were clustered into another category. These results showed that the PAL sequences of the majority tartary buckwheat samples was stable and the differences between the most samples was not significant. The samples in Sichuan province had abundant genetic diversity. But only in samples from Tibet it revealed many SNPs site,and this should be the new mutation spots in the PAL coding regions.